TEACHING FINANCIAL LITERACY IN PRIMARY SCHOOL STUDENTS: INTERNATIONAL EXPERIENCE - Viktoriia Andriichuk (Неперервна професійна освіта: теорія та практика)
The article is devoted to international experience in teaching financial literacy in elementary school students. The state of research is analyzed in the theory and practice of elementary education. This article reacts to the current situation in our society and the need for financial education in schools. The modern world requires financial and economic literacy.